2005
DOI: 10.1038/sj.onc.1208851
|View full text |Cite
|
Sign up to set email alerts
|

Sodium butyrate sensitizes human glioma cells to TRAIL-mediated apoptosis through inhibition of Cdc2 and the subsequent downregulation of survivin and XIAP

Abstract: In TNF-related apoptosis-inducing ligand (TRAIL)-resistant glioma cells, co-treatment with nontoxic doses of sodium butyrate and TRAIL resulted in a marked increase of TRAIL-induced apoptosis. This combined treatment was also cytotoxic to glioma cells overexpressing Bcl-2 or Bcl-xL, but not to normal human astrocytes, thus offering an attractive strategy for safely treating resistant gliomas. Cotreatment with sodium butyrate facilitated completion of proteolytic processing of procaspase-3 that was partially bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
51
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(54 citation statements)
references
References 58 publications
2
51
1
Order By: Relevance
“…However, of major interest was our finding that apoptosis and therapeutic activity, mediated by the combination of MD5-1 and vorinostat, was also significantly suppressed by CrmA and c-FLIP, whereas overexpression of Bcl-2 had little or no effect. These data clearly demonstrated that vorinostat enhanced the apoptotic activity of MD5-1 in the extrinsic pathway and is consistent with other studies that make similar conclusions (25,26). However, there are other reports indicating that synergistic tumor cell apoptosis, mediated by the combination of HDACi and TRAIL activating agents, requires both the extrinsic and intrinsic pathways (27)(28)(29).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…However, of major interest was our finding that apoptosis and therapeutic activity, mediated by the combination of MD5-1 and vorinostat, was also significantly suppressed by CrmA and c-FLIP, whereas overexpression of Bcl-2 had little or no effect. These data clearly demonstrated that vorinostat enhanced the apoptotic activity of MD5-1 in the extrinsic pathway and is consistent with other studies that make similar conclusions (25,26). However, there are other reports indicating that synergistic tumor cell apoptosis, mediated by the combination of HDACi and TRAIL activating agents, requires both the extrinsic and intrinsic pathways (27)(28)(29).…”
Section: Discussionsupporting
confidence: 82%
“…However, a recent study provides compelling evidence that although HDACi can indeed induce expression of TRAIL and/or its cognate receptors, this event is not necessary to mediate synergistic apoptosis of target cells by using a combination of HDACi and recombinant TRAIL or anti-DR4/DR5 mAbs (33). Other studies have correlated synergistic tumor cell apoptosis by HDACi and activators of the TRAIL pathway with decreased expression of c-FLIP (8,25), decreased expression of apoptosis inhibitors and Bcl-2 (25), inhibition of Cdc2 protein and subsequent down-regulation of survivin and XIAP (26), and modulation of NF-B activity (28,34,35). It is not yet clear whether a common molecular event will be identified as being requisite to mediate synergistic apoptosis by HDACi and TRAIL activators, or whether the responses will depend on the cell type and/or HDACi under investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, HDACI-mediated sensitization to TRAIL has been described in various solid and hematological cancer cell lines, 36 --40 including one report in glioblastoma. 41 In the present study, we show for the first time that MS275 enhances TRAILinduced apoptosis in primary cultured glioblastoma cells in addition to several established cell lines. Our data proposing MS275 as a suitable combination partner for TRAIL are supported by a recent publication showing that MS275 as single agent inhibits the growth of glioma-derived neurospheres.…”
Section: Discussionmentioning
confidence: 85%
“…When TRAIL cross-links with its death receptors, DR4 or DR5, the death receptors oligomerize and trigger the recruitment of Fas-Associated protein with Death Domain (FADD), the activation of caspase-8, and the subsequent initiation of apoptosis (Kischkel et al, 2000). However, recent studies have shown that many cancer cells, including glioma cells, are resistant to TRAILinduced apoptosis even though they express TRAIL receptors (Hao et al, 2001;Kim et al, 2005). Thus, the development of new therapeutic strategies to restore TRAIL-induced apoptosis in cancer cells will be required to improve the efficacy of TRAIL-based cancer therapy.…”
Section: Introductionmentioning
confidence: 99%